Neuronal prolyl-4-hydroxylase 2 deficiency improves cognitive abilities in a murine model of cerebral hypoperfusion - Gruneberg, Daniel; Montellano, Felipe Andrés; Plaschke, Konstanze; Li, Lexiao; Marti, Hugo; Kunze, Reiner (Experimental neurology, 2016)
Episodes of cerebral hypoxia/ischemia increase the risk of dementia, which is associated with impaired learning and memory. Previous studies in rodent models of dementia indicated a favorable effect of the hypoxia-inducible factor (HIF) targets VEGF (vascular endothelial growth factor) and erythropoietin (Epo). In the present study we thus investigated whether activation of the entire adaptive HIF pathway in neurons by cell-specific deletion of the HIF suppressor prolyl-4-hydroxylase 2 (PHD2) improves cognitive abilities in young (3months) and old (18-28months) mice suffering from chronic brain hypoperfusion. Mice underwent permanent occlusion of the left common carotid artery, and cognitive function was assessed using the Morris water navigation task. Under conditions of both normal and decreased brain perfusion, neuronal PHD2 deficiency resulted in improved and faster spatial learning in young mice, which was preserved to some extent also in old animals. The loss of PHD2 in neurons resulted in enhanced hippocampal mRNA and protein levels of Epo and VEGF, but did not alter local microvascular density, dendritic spine morphology, or expression of synaptic plasticity-related genes in the hippocampus. Instead, better cognitive function in PHD2 deficient animals was accompanied by an increased number of neuronal precursor cells along the subgranular zone of the dentate gyrus. Overall, our current pre-clinical findings indicate an important role for the endogenous oxygen sensing machinery, encompassing PHDs, HIFs and HIF target genes, for proper cognitive function. Thus, pharmacological compounds affecting the PHD-HIF axis might well be suited to treat cognitive dysfunction and neurodegenerative processes.